Workplace Bullying: The Workers Understanding About Violence - Nunes, Thiago Soares (2018)
Workplace bullying is an old situation. However, in the last few decades it was actually identified as a destructive work environment, not only causing a decrease in productivity, but also favoring the absenteeism due to the effects/consequences that it causes (Hirigoyen, 2008). One of the major difficulties to fight against and prevent violence is information about it, the concept and its characteristics. The purpose of this article was to describe the definition of workplace bullying from participants´ answers about the topic in a term/word. In order to do so, three surveys that occurred in 2008, 2010 and 2014-2015 were used, with participants from many sectors, such as banking, health system, justice, education, technical and administrative roles, and others. As a conclusion, the participants primarily defined workplace bullying as hostile practice aspects, such as humiliation, disrespect, abuse; and in sequence as a consequence/effect such as shame, fear, anger. It was also verified that there is similarity of the terms used by the research participants from 2008 to 2015.